Study of the Radiosensitizing Action of Lithium Ascorbate Under Neutron and Photon Irradiation of Tumor Cells - M. S. Tretyakova; A. G. Drozd; M. V. Belousov; K. S. Brazovskiy; M. S. Larkina; S. V. Krivoshchekov; A. A. Artamonov; I. A. Miloichikova; A. V. Bezmaga; A. M. Bolshakov; E. S. Sukhikh; E. V. Plotnikov (Разработка и регистрация лекарственных средств, 2023)
Introduction. Radioresistance of cancer cells is a serious problem in radiation therapy of tumor diseases. Radiosensitizers make malignant cells more sensitive to radiation and increase the effectiveness of radiation therapy; however, their widespread clinical use is limited by significant side effects. The development and study of new radiosensitizers seems to be an urgent task of modern pharmacology.Aim. The purpose of this work was to study the effectiveness of lithium ascorbate as a radiosensitizer under the influence of photon and neutron radiation in wide dose range.Materials and methods. Evaluation of the biological effect was carried out using the tumor line of prostate cancer PC-3. We used a cyclotron to produce neutron radiation and a Cobalt-60 source to produce gamma radiation.Results and discussion. We have proved an increase in the cytotoxic effect with the combined use of different types of ionizing radiation and lithium ascorbate. The resistance of the prostate cancer line to gamma radiation at an absorbed dose of 0.5–3.0 Gy was revealed. It was shown that tumor cells of prostate cancer are more sensitive to the effects of the study drug in minimal concentrations in combination with neutron irradiation compared to gamma radiation in the same absorbed dose. The main mechanism of the radiosensitizing action of lithium ascorbate is the local induction of oxidative stress, which synergistically enhances the action of ionizing radiation.Conclusion. The combination of lithium ascorbate with neutron radiation leads to a more pronounced resulting cytotoxic effect. An increase in the concentration of lithium ascorbate led to the pro-oxidative action with an increase in the damaging effect on cells.